Serum 25(OH)D levels are associated with disease activity and renal involvement in initial-onset childhood systemic lupus erythematosus - Jiang, Lijun; Zhi, Shufeng; Wei, Chenxi; Rong, Zanhua; Zhang, Huifeng (Frontiers in Pediatrics, 2023)
Background: Vitamin D deficiency is common in patients with systemic lupus erythematosus (SLE) and may affect their disease activity and severity. Objective: This study aims to assess the vitamin D status in patients with initial-onset SLE during childhood and its association with the clinical and laboratory markers of disease activity. Method: This is a retrospective study that includes 168 patients with initial-onset SLE during childhood and 109 healthy children as controls. Clinical and laboratory data were recorded. The area under the curve (AUC) method was used to evaluate the efficacy of double-stranded deoxyribonucleic acid (dsDNA), lower (25[OH]D) and complement 3 (C3) alone and in combination to diagnose the presence of renal damage in children with SLE. Result: Compared with the controls (25.53±7.02 ng/ml), patients with initial-onset SLE during childhood have lower serum 25(OH))D levels (18.63±5.32 ng/ml) (P<0.05). Among patients with initial-onset SLE during childhood, SLEDAI-2K scores are significantly higher in the vitamin D insufficiency (median=14.5) and vitamin D deficiency (median=14.0) groups than in the vitamin D sufficiency group (median=9.0) (P<0.05). Patients with initial-onset SLE during childhood with lower 25(OH)D levels are more likely to have lupus nephritis (LN) and a higher (SDI) score (P<0.05). Compared with patients with other types of LN (16.69±3.90 ng/ml), patients with type V LN have lower levels of 25(OH)D (12.27±3.53 ng/ml) (P<0.05). The AUC was 0.803 when dsDNA antibody, 25(OH)D level and C3 were used in combination to diagnose LN in patients with SLE. Conclusion: Vitamin D deficiency and insufficiency are closely related to an increase in SLEDAI and SDI scores. Significant decrease in vitamin D level is a risk factor for LN.